(untitled) (Journal of Hama University, 2019)
Studies have shown that retention loss of glass fiber reinforced post (GFRP) is the predominant failure mode in glass ﬁber post-retained restorations. Alternatives to resin-based luting cements that have been advocated include glass-ionomer cement (GIC) and resin-modiﬁed glass-ionomer cement (RMGIC), especially due to their chemical adhesion ability to tooth structures. Conditioning with poly-acrylic acid solutions is considered one of the most techniques used because its role in remove of the smear layer from dentine before using glass Ionomer cement. This study has been achieved to evaluate the effectiveness of the poly acrylic acid in Conditioning root canal dentine before bonding glass fiber reinforced posts by glass ionomer cement. Eighteen mandibular premolars were endodontically treated. All teeth were cut above cement-enamel junction with 2 mm. The root canals were enlarged to the same length and width using a special reamer. The sample was divided into 3 groups according to the bonding technique. The chemical curing resin cement used in the first group (Control group), and GIC used in the second. The root canals were conditioned by Poly acrylic acid in third group, then GIC was used in bonding the glass fiber reinforced posts. All specimens were subjected to a pull-out bond strength test in a universal testing machine at a crosshead speed of 0.5 mm/min. The results, in newton, were analyzed with T-Student test. The median of failure strength for all groups were (68.95 +_2.47 , 113.84+_ 21.44 , 97.53 +_ 11.79 N ) respectively. T-student test showed that There were no significant difference between second and third groups (GIC, GIC with conditioner). But bond strength in second and third groups were better than the first(resin cement) . Conditioning root canal surface by Poly-acrylic acid 10% before bonding the glass fiber reinforced post using GIC didn’t effect on the bond strength of posts to root canal. Using GIC with or without dentin conditioning by Poly-acrylic acid improved bond strength comparatively with chemical cured resin cement.